Reviewing the current treatment approaches for bullous pemphigoid – analysis of literature - Julia Nowak; Agnieszka Najdek; Daria Oleksy; Dawid Komada; Urszula Kaczmarska; Aleksandra Woźniak; Michał Jakub Cioch; Marcin Mycyk; Kamil Hermanowicz; Katarzyna Doman (Journal of Education, Health and Sport)
Bullous pemphigoid (BP) is an autoimmune blistering disorder primarily affecting the elderly, particularly older men, and is characterized by type 2 inflammation. The disease is defined by autoantibodies targeting BP180 (BPAG2) and BP230 (BPAG1) within the basement membrane zone. Advanced age is a significant risk factor for BP, with additional associations identified, including certain medications—such as dipeptidyl peptidase-4 inhibitors and aldosterone antagonists—and neurological disorders like Parkinson’s disease. The global annual cumulative incidence of BP is estimated at 8.2 cases per 1,000,000 individuals, with Europe reporting higher incidence rates than other regions. BP significantly impacts patients’ quality of life due to painful, pruritic skin lesions and is associated with a higher prevalence of psychiatric comorbidities, such as schizophrenia. BP increases the risk of complications, including pulmonary embolism and pneumonia, and is linked to high mortality. These findings highlight the need for early diagnosis and comprehensive management to improve patient outcomes.